MO1002EFFICACY OF PLASMAPHERESIS IN KIDNEY TRANSPLANT PATIENTS WITH FOCAL SEGMENTAL GLOMERULOSCLEROSIS : A SINGLE CENTER EXPERIENCE. (29th May 2021) - El Meknassi, Imen; Dorsaf, Zellema; Awatef, Azzabi; Wissal, Sahtout; Narjes, Ben Aicha; Sanda, Mrabet; Asma, Fradu; Sabri, Ferdaous; Ben Amor, Samira; Yosra, Guedri; Abdellatif, Achour
Abstract: Background and Aims: Plasmapheresis (PP) have been used in kidney transplant (KT) patients for multiple immunological renal diseases. Focal segmental glomerulosclerosis (FSGS) is one of the most prevalent indication for PP. It can be used either for curative or preventive treatment of its recurrence. The aim of our study was to assess the outcomes of PP among KT patients with FSGS. Method: We performed a retrospective study including all KT patients with FSGS who underwent PP during the period from December 2007 to December 2018. PP was performed using a filtration technique by a Prismaflex machine. Results: Among 275 KT patients, we have identified 5 patients with FSGS who underwent PP either before or after transplantation. The mean age was 26.4 years. All patients but one received a living-donor kidney with number of mismatches between 3 and 5. All patients were under corticosteroids, mycophenolate mofetil and cyclosporine. Two patients presented recurrent FSGS within 3 days following the transplantation. Mean serum creatinine level and proteinuria before PP were 517 ±191 µmol/l and 17.7 ±7.5 g/day respectively. The PP was used basing on Canaud protocol combined to rituximab. The mean number of PP sessions was 29. Only one patient required hemodialysis. None of the patients had lost his graft. The mean serum creatinine level was 172±55 µmol/l. One patient died of septic shock. PP was used in two other patients before transplantation in order to prevent the recurrence of FSGS. They have preserved a normal kidney function after a period of follow-up (37 months and 7 years). No rejection or recurrence of FSGS was noted during the follow-up period. Another patient aged 20, underwent 5 sessions of PP on alternate days immediately after transplantation to prevent the recurrence of FSGS. His baseline serum creatinine level was at 136 µmol/l. The recurrence of his initial renal disease occurred after 21 months requiring other sessions of PP. Rituximab was tried but stopped in front of allergy reaction. His renal function remained stable. Overall, PP was well tolerated in all patients with no incident. Conclusion: Recurrence of the FSGS after transplantation is a concern for nephrologists due to the difficulty of treatment. Our study shows the efficacy of plasmapheresis before kidney transplantation to prevent recurrence of FSGS.